Differential Impact of T-bet and IFNγ on Pancreatic Islet Allograft Rejection. Issue 9 (September 2018) - Besançon, Alix; Demir, Zeynep; Goncalves, Tania; Valette, Fabrice; Panafieu, Emilie; Chatenoud, Lucienne; You, Sylvaine
Abstract : Background: T cell–mediated graft rejection is mostly correlated with potent Th1 responses. However, because IFNγ −/− mice reject their graft as efficiently as wild-type (WT) mice, the exact contribution of IFNγ and its transcription factor T-bet remains a matter of debate. Here, we address this question in the context of pancreatic islet allograft to better inform the molecular pathways that hampers islet survival in vivo. Methods: Pancreatic islets from BALB/c mice were transplanted in WT, IFNγ −/−, or T-bet −/− C57BL/6 mice. Graft survival and the induction of effector and cytotoxic T-cell responses were monitored. Results: Rejection of fully mismatched islet allografts correlated with high expression of both IFNγ and T-bet in WT recipients. However, allogeneic islets were permanently accepted in T-bet −/− mice, in contrast to IFNγ −/− hosts. Long-term survival correlated with decreased CD4 + and CD8 + T-cell infiltrates, drastically reduced donor-specific IFNγ and tumor necrosis factor tumor necrosis factor α responses and very low expression of the cytotoxic markers granzyme B, perforin, and FasLigand. In addition, in vitro and in vivo data pointed to an increased susceptibility of T-bet −/− CD8 + T cell to apoptosis. These observations were not reported in IFNγ −/− mice, which have set up compensatory effector mechanisms comprising an increased expression of the transcription factor Eomes and cytolytic molecules as well as tumor necrosis factor α–mediated but not IL-4 nor IL-17–mediated allogeneic responses. Conclusions: Anti-islet T-cell responses require T-bet but not IFNγ-dependent programs. Our results provide new clues on the mechanisms dictating islet rejection and may help refine the therapeutic/immunosuppressive regimens applied in diabetic patients receiving islets or pancreas allografts. Abstract : Besançon et al report that T-bet-deficient recipients spontaneously accept allogeneic pancreatic islets, whereas IFNγ-deficient recipients retain their ability to reject due to expression of compensatory effector mechanisms comprising increased Eomes, cytolytic molecules, and TNFα. Supplemental digital content is available in the text.